MUSYARAKAH IN ISLAMIC ACCOUNTING PERSPECTIVE CONCEPT AND APPLICATION - Latifah, Eny; Wijayanti, Iin; Zulfa W, Khusnatul; Yusuf, Yusuf (Journal Economics Technology And Entrepreneur, 2025)
This study aims to analyze the basic concept of musyarakah contract according to sharia principles and its implementation in the accounting practices of Islamic financial institutions, especially based on Sharia Financial Accounting Standard (PSAK) No. 106. The research method used is a literature study with a descriptive-analytical approach, examining the theoretical basis of literature sources and implementation reports in several Islamic financial institutions. The results show that the application of musyarakah contracts in accounting requires separate recording of assets and liabilities arising, measurement of musyarakah investments at the fair value of non-cash assets delivered, and transparent recognition of profit-sharing income and expenses. Although the basic principles are clearly defined in shariah, challenges in accounting implementation often arise related to transparency issues, difficulties in business feasibility analysis, and the diversity of musyarakah products (e.g., mutanaqisah or declining musyarakah). Alignment between sharia concepts and accounting standards (PSAK 106) is essential to ensure fair and transparent practices. A deep understanding by practitioners of Islamic Financial Institutions is required to ensure sharia compliance and accountable presentation of financial statements.